(untitled) (Plant Tissue Culture and Biotechnology, 2026)
The current study aims to examine pathogenic fungi responsible for leaf blight disease in garlic and to investigate their classical and molecular identification, mycelial growth, and biological control using antagonistic fungi and plant extracts. Curvularia geniculata is a dematiaceous septate hyphal fungus producing brown, geniculate conidia and dark-brown mycelium, providing the initial evidence. Results from a 576 bp polymerase chain reaction (PCR) were obtained from the isolated C. geniculatus internal transcribed spacer (ITS) region using universal primers, ITS1 and ITS2. The molecular phylogenetic tree constructed from it revealed that the C. geniculatus species complex had 100% sequence similarity. The optimum pH and temperature were recorded at 7.0 and 30°C, respectively, for the mycelial growth of C. geniculatus. The experimental findings revealed that the antagonistic fungus Trichoderma reesei exhibited the greatest (93.29%) growth inhibition against C. geniculatus, followed by T. asperellum (83.52%) and T. harzianum (65.57%). The Lawsonia inermis and Ocimum tenuiflorum plant extracts are significantly effective against C. geniculatus, the causative agent of garlic leaf blight, at a 30% (v/v) concentration rate. Plant Tissue Cult. & Biotech. 35(2): 335-346, 2025 (December)